Equine sarcoid treatment: Report of four clinical cases (Ciencias Veterinarias, 2015)
Sarcoid is the most common skin tumor in horses, with different presentations and locations on the skin. This study is aimed at describing the presentation, approach and evolution of four clinical cases of equine sarcoid in Costa Rica. The treatment implemented is described, as well as the subsequent evolution of these cases treated with surgical removal, cauterization and autologous vaccine. Two male horses, ages three and six, with lesions in the foreskin and inguinal area, received a combined therapy with surgical removal, cauterization and two doses of autologous vaccine. A third horse, seven years old, with a lesion on the lip, and a mare, eight years old, with a mass in the right forelimb over the radius, were treated with surgical removal and cauterization. Even though all patients developed a favorable clinical response to their treatments, those treated with surgical removal, cauterization and autologous vaccine showed no relapse compared to the other equines that were treated exclusively with surgical removal and cauterization.